Effect of Laparoscopic Sleeve Gastrectomy on Thyroid Hormones in Euthyroid Obese Patients - Ozsoy, Zeki; Kutluturk, Faruk (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2018)
Introduction: In obese patients, the incidences of several thyroid disorders have increased in comparison to the general population. This study is aimed to investigate the effect of laparoscopic sleeve gastrectomy (LSG) on thyroid function tests in obese patients. Methods: The patient files of 186 individuals who underwent laparoscopic sleeve gastrectomy surgery were examined retrospectively. Forty-nine females and 29 males comprising a total of 78 patients were included in the study. The routine physical examination findings and laboratory parameters recorded preoperatively were compared with their counterparts obtained in the postoperative sixth month. Results: The mean preoperative body mass index (BMI) levels of the patients in the study was calculated as 46.91 kg/m2, whereas the mean BMI in the postoperative sixth month was 30.35 kg/m2 (p<0.001). Prior to the sleeve gastrectomy, the mean thyroid stimulating hormone (TSH) level of the patients was 2.53 ±2.06 μIU/mL; however, a significant reduction was observed in the mean TSH level during the postoperative sixth month, which was calculated as 1.77 ±1.12 μIU/mL (p=0.015). The mean free T4 level was 1.18±0.1 ng/dL in the preoperative period, but this increased to 1.22 ±0.24 ng/dL postoperatively, an insignificant change. The decrease in the TSH levels after the LSG was determined not to be correlated with the decrease in body weight. Conclusion: The results of our study demonstrate that the levels of TSH decreased significantly in patients who underwent LSG and that the decrease was independent of the changes in BMI.
Keywords: sleeve gastrectomy